The role of “fake” past tense in acquiring counterfactuals - Tulling, Maxime A.; Cournane, Ailís (Proceedings of the Amsterdam Colloquium, 2019)
Prior research on the acquisition of counterfactuals has not considered the mapping challenges associated with past tense morphology, which refers either to the actual past or a ”fake” past expressing counterfactuality. In a corpus study of children’s spontaneous productions of counterfactual constructions, we found that wish-constructions are acquired before counterfactual conditionals, and that children make productive tense errors in counterfactuals producing present tense marking instead of past. These errors cease around the time children start producing wish-constructions that unequivocally display counterfactual reasoning, and could reflect a stage where children are still figuring out that counterfactual past tense does not signal a past event on the timeline, but rather a present non-actuality.